Hubungan Antara Kecerdasan Emosional Dengan Perilaku Agresif Pada Santri Pondok Pesantren - Kurniawan, Ilham; Husin, Lauditta Soraya; Rasyidin, Yusyafrida; Islamia, Intan (ANFUSINA: Journal of Psychology, 2019)
Pesantren is an Islamic educational institution that aims to develop students into generations who have high knowledge and are able to carry out Islamic aqeedah and sharia, but in the environment of Islamic boarding schools are still often found negative behaviors such as aggressive behavior committed by teenage students. This is because teenagers are often less able to control emotions. One factor the cause of the emergence of aggressive behavior is the low level of emotional intelligence. Individuals who have low emotional intelligence tend to be aggressive. This study aims to determine the relationship between emotional intelligence with aggressive behavior in Islamic boarding school students. The subjects in this study were eighth grade Muslim students of MTs who lived in the Al-Fatah Islamic Boarding School dormitory in 2018/2019, totaling 60 students taken with total sampling techniques. The method of data collection in this study uses two psychological scales namely the aggressive behavior scale of 24 items (α = 0.881) and the emotional intelligence scale of 26 items (α = 0.933). Data that has been collected later analyzed using the product moment correlation analysis technique which is assisted with SPSS 21.0 for Windows. The results showed rxy = -0,454 with p = 0,000 (p <0.01), this indicates that there is a significant and negative relationship between emotional intelligence with aggressive behavior in Al-Fatah Islamic boarding school students so that the hypothesis is accepted, the lower the emotional intelligence owned by students, students tend to have high aggressive behavior and vice versa with an effective contribution of 20.6% which is influenced by the independent variables in this study and 79.4% are influenced by variables outside the study.